2006
DOI: 10.1592/phco.2006.26.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Osmol Gap as a Surrogate Marker for Serum Propylene Glycol Concentrations in Patients Receiving Lorazepam for Sedation

Abstract: Osmol gap can be used as a surrogate marker for serum propylene glycol concentration. In critically ill patients receiving lorazepam for sedation, an osmol gap above 10 was associated with concentrations previously reported to cause toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 105 publications
1
57
2
Order By: Relevance
“…The dosing threshold for this effect has not been prospectively defined, but doses exceeding 20 mg/h and continued for longer than 4 weeks, and higher doses (Ͼ25 mg/h) continuing for hours to days have been proposed (Laine et al, 1995;Seay et al, 1997;Arbour, 1999). Toxicity from propylene glycol has been attributed to direct effects and its metabolites, lactate and pyruvate (generated by hepatic alcohol dehydrogenase), resulting in hyperosmolar states, cellular toxicity, metabolic acidosis, and acute tubular necrosis (Barnes et al, 2006).…”
Section: Benzodiazepines In the Intensive Care Unitmentioning
confidence: 99%
“…The dosing threshold for this effect has not been prospectively defined, but doses exceeding 20 mg/h and continued for longer than 4 weeks, and higher doses (Ͼ25 mg/h) continuing for hours to days have been proposed (Laine et al, 1995;Seay et al, 1997;Arbour, 1999). Toxicity from propylene glycol has been attributed to direct effects and its metabolites, lactate and pyruvate (generated by hepatic alcohol dehydrogenase), resulting in hyperosmolar states, cellular toxicity, metabolic acidosis, and acute tubular necrosis (Barnes et al, 2006).…”
Section: Benzodiazepines In the Intensive Care Unitmentioning
confidence: 99%
“…Rare propylene glycol toxicity that leads to idiosyncratic lactic acidosis has been described following administration of lorazepam, diazepam, nitroglycerin, and etomidate, which are dispensed in propylene glycol solvent in the intensive care setting. Other drugs that contain propylene glycol in clinically relevant amounts include pentobarbital, trimethoprim-sulfamethoxazole, esmolol, phenytoin, phenobarbital, and dimenhydrinate [77][78][79][80], Consequently, propylene glycol toxicity should be considered in any patient with lactic acidosis receiving a propylene-glycol-containing medication, particularly when the patient is on multiple such drugs for long periods of time, has underlying risk factors for toxicity such as liver disease, kidney disease, or pregnancy, or is less than 4 years old [81].…”
Section: Medicationsmentioning
confidence: 99%
“…Osmolal gap at 48 hours is considered to be the strongest marker of propylene glycol concentration; by contrast, anion gap and serum lactate concentrations are poor indicators. 1,2,18 Arroliga et al showed significant correlation between the rate of high-dose lorazepam infusion, serum propylene glycol level and serum osmolality at 48 hours (Figures 1 and 2). Serum propylene glycol concentration can be predicted using the following equation: serum propylene glycol concentration (mg/dl) = -82.1 + (osmolal gap [mmol/kg] × 6.5).…”
Section: Clinical Presentation Of Propylene Glycol Toxicitymentioning
confidence: 94%
“…[1][2][3][4]17,18 Clinical presentation of this condition varies widely, however, sometimes even mimicking sepsis or systemic inflammatory response syndrome (Box 1). 1 If unrecognized and left untreated, the toxic effects of propylene glycol can progress from metabolic acidosis to fatal multiorgan failure.…”
Section: Clinical Presentation Of Propylene Glycol Toxicitymentioning
confidence: 99%